Hubungan Lingkungan Sosial dan Media Massa dengan Kejadian Menarche Dini pada Anak Sekolah Siswi Kelas V dan VI di SDN 205 Kota Baru Kota Jambi Tahun 2018 - Hasyim Kadri; Salvita Fitrianti (Universitas Batanghari Jambi, 2019)
Menarche is the beginning of menstruation in a girl during puberty, which usually appears at the age of 11-14 years. Menarche is a sign of a change in the social status of children to adulthood, young women who have the tendency of neurotic in pubertal age many have an inner conflict with the advent of the first menstruation that can cause Pathological behavior (Sukarni K, DKK 2013), the occurrence of Menarche in every woman is not the same because there are several factors influencing it, such as socio-economic factors, heredity, social environment and also health factor and nutritional status. Fat-headed young women usually tend to experience Menarche earlier than in the thin-body young women (Andira, D. 2010). Research aims to be knew social environment relations, and mass Media with the event of early Menarche in school students class V and VI SDN 205 kota Baru City of Jambi. The design of this research is an effective method of research with analytic surveys, using the Cross Sectional approach. The population in this study is all students of class V and VI that Menarche early at SDN 205 Kota Jambi. The samples in this study were all (Total Sampling) of class V and VI who had Menarche at SDN 205 Kota Jambi which amounted to 45 respondents. In this insulation conducted analysis of Univariat, Bivariat. he results of the analysis gained that there is a social environment (p value 0.000) and mass media (p value 0.002). It is recommended to further improve the counseling on early Menarche as well as Menarche pain to the students and more activating UKS activities.